Factors associated with adherence to haart, in patients with hiv / aids in at the central hospital of the police forces - -Zanabria, Gustavo Eugenio Orellana (2019)
Objective: To determine the associated factors and the degree of adherence to HAART in patients with HIV / AIDS in the Central Hospital PNP "Luis N. Sáenz" in the months of October to December 2015. Methods: Observational, cross-sectional, analytical and descriptive study where 123 patients were evaluated with a CEAT-HIV questionnaire. The data collection was done in the Microsoft Excel program and the statistical analysis through the SPSS program v.22. Results: We found that the average age of all the patients evaluated was 40.11 years. The infection time of the patients evaluated was an average of one year and 7 months. The treatment time with the HAART consisted of an average of 20 months. The 52% (64 patients) of the studied population was a family member of the holder, whether wife (or), child (ren) or parents. The gender that prevails in the sample is male with 63.4% (78 patients). And viral load, 77.2% is undetectable (<400 copies /ml). The degree found was an adequate adherence to HAART, with a score of 82.51, and when relating the degree of adherence with the socio-demographic characteristics they are not significant. But if the degree of adherence with viral load was found to be related. Conclusion: The studied population has an adequate adherence to antiretroviral treatment and the 5 factors that the questionnaire measures: compliance with the treatment, history of lack of adherence, doctor-patient interaction, beliefs of the patient and strategy for taking medications, they have very good influence on adherence to HAART.   DOI:  10.25176/RFMH.v19.n1.1792